Approaches for dislodged stent retrieval during transradial percutaneous coronary interventions. Issue 6 (12th November 2012) - Kwan, Tak W.; Chaudhry, Muhammad; Huang, Yili; Liou, Michael; Wong, Sally; Zhou, Xuanjing; Pancholy, Samir; Patel, Tejas
<x xml:space="preserve">Abstract</x> Transradial percutaneous coronary intervention (PCI) has been associated with a lower incidence of major access site related complications. With the increased implementation of transradial approach in complex PCI, stent dislodgement is unavoidable in any interventionalists' career. Stent retrieval is different in a transradial approach as compared to a transfemoral approach because of the former's smaller arterial size. In this review, we outline the different stent retrieval techniques with considerations from transradial access. © 2012 Wiley Periodicals, Inc.